Audit committee structure and earnings management in Asia Pacific - Yasser, Qaiser Rafique; Mamun, Abdullah Al (Economics and Business Review, 2016)
The relationships between the audit committee structure and earnings management is quite complicated. They are not simply bivariate correlations. Rather, there may be mediating effects or moderating influences on these casual associations. Nonetheless, previous research has not investigated these complicated relationships in emerging markets with an advanced economy. This paper aims to examine the mediating impact of audit committee structure and earnings management in Australia, Malaysia, and Pakistan. The results suggest that audit committee size is positively associated with financial reporting quality. We also noted that, instead of adding value, audit committee independence is negatively associated with reporting quality. The results indicate that the audit committee is a less significant factor in corporate governance than suggested by many previous researchers and policy makers. This paper contributes to the literature on corporate governance and earnings management by introducing a framework for identifying and analyzing moderating variables that affect the relationship between the audit committee structure and earnings management.